Sunni Islamic perspectives on lab-grown sperm and eggs derived from stem cells–in vitro gametogenesis (IVG) - Serour, Gamal; Ghaly, Mohammed; Shaikh, Mohd Saifuddeen; Ayaz, Anwar *; Noor Munirah, Isa; Heng, Alexis Boon Chin (Taylor and Francis Group, 2023)
An exciting development in the field of assisted reproductive technologies is In Vitro Gametogenesis (IVG) that enables production of functional gametes from stem cells in the laboratory. Currently, development of this technology is still at an early stage and has demonstrated to work only in rodents. Upon critically examining the ethical dimensions of various possible IVG applications in human fertility treatment from a Sunni Islamic perspective, together with benefit-harm (maslahah-mafsadah) assessment; it is concluded that utilization of IVG, once its efficacy and safety are guaranteed, could be permissible by strictly adhering to Islamic ethical principles related to marriage, biological/genetic relatedness, sexual intercourse, and moral status of the embryo/fetus versus that of the gamete. As a result, IVG will be acceptable for treating primary infertility, age-related infertility, and preventing genetic diseases. However, it will be unacceptable for application in posthumous reproduction, donor gametes, genetic enhancement, and procreation in same-sex couples.